Bifidobacterium bifidum CCFM1389 Regulates Intestinal Motility Disorder by Repairing the Enteric Nervous System and Intestinal Barrier - HUANG Yin, LI Jiazhen, LIU Wenxu, XUE Yifan, ZHU Shengnan, WANG Linlin, WANG Gang (Shipin Kexue, 2025)
A pseudo-germ-free mouse model was constructed using broad-spectrum antibiotics (ABX) to investigate their effects on intestinal motility and the enteric nervous system (ENS) in mice. Bifidobacterium bifidum CCFM1167 was used as a positive strain, and another four B. bifidum strains were screened and evaluated for their regulatory effects on intestinal dysfunction and the ENS. 16S rDNA gene sequencing was used to detect changes in the gut microbiota, and hematoxylin-eosin (H&E) staining and real-time polymerase chain reaction (PCR) were employed to characterize the damage of the ENS and the intestinal barrier. The results showed that ABX treatment significantly affected the intestinal structure and function of mice, leading to altered intestinal morphology, slowed motility and increased fecal water content, accompanied by a severe imbalance in the gut microbiota and damage to the ENS and the intestinal barrier. After intervention with B. bifidum CCFM1389, a significant reduction in total intestinal transit time was observed, and fecal water content returned close to the normal level, along with the alleviation of intestinal motility disorders. Additionally, CCFM1389 significantly increased the gene expression levels of specific markers for colonic neurons (PGP9.5) and enteric glial cells (S100β and GFAP), indicating a repairing effect on the ENS. CCFM1389 also significantly elevated the gene expression of tight junction proteins (Occludin, Claudin-3 and ZO-1), alleviating intestinal barrier damage, and its effect was more pronounced than that of the positive strain CCFM1167. Furthermore, CCFM1389 regulated the structure and composition of the gut microbiota, maintaining intestinal microbial homeostasis. Spearman correlation analysis indicated that CCFM1389 effectively modulated ABX-induced intestinal motility disorders, possibly by increasing the increase in the relative abundance of beneficial bacteria such as Akkermansia, Bifidobacterium, and Lachnoclostridium while decreasing the relative abundance of pathogenic bacteria such as Escherichia_Shigella and Enterococcus, thereby repairing the ENS and the intestinal barrier and regulating intestinal motility.